Strategi Insentif dan Sanksi dalam Meningkatkan Kinerja Pegawai di Lingkungan Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Provinsi Gorontalo - Thantri Bakari; Andi Yusniar Mendo; Mohamad Agus Salim Monoarfa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines how reward and punishment affect employee performance in the Regional Office of the Ministry of Law and Human Rights of Gorontalo Province. Data collection techniques in this study used a questionnaire with a population of all Civil Servants (PNS) at the Regional Office of the Ministry of Law and Human Rights Gorontalo, with as many as 121 employees. The sampling used probability sampling, with a sample size of 93 respondents, through the Slovin formula. Data analysis techniques used multiple linear regression analysis model via SPSS 26 application.According to the multiple regression analysis tests, it was found that the simultaneous results of the reward and punishment variables affect performance. This result is evidenced by the percentage of the performance variable of 32,5%, while the remaining 67,5% is affected by other variables not examined and explained in this study.